Coexistence of blaKPC-2–IncN and mcr-1–IncX4 plasmids in a ST48 Escherichia coli strain in China - Yanfei Wang; Haiyang Liu; Qian Wang; Xiaoxing Du; Yunsong Yu; Yan Jiang (Journal of Global Antimicrobial Resistance, 2020)
Objectives: The aim of this study was to explore the genomic content of a blaKPC-2- and mcr-1-harbouring Escherichia coli strain and to clarify the molecular mechanism for the transmission of multidrug resistance. Methods: Antimicrobial susceptibility testing was conducted by the broth microdilution method to determine the resistance profile. Filter-mating conjugation assays were performed to confirm the plasmid transfer ability. Whole-genome sequence data were acquired by a combination of Illumina paired-end reads and Nanopore long-read sequencing. Results: Escherichia coli strain QE11−421 was an mcr-1-positive colistin-resistant isolate that co-harboured the blaKPC-2 gene conferring carbapenem resistance. Genome sequence data confirmed QE11−421 as a sequence type 48 (ST48) E. coli that harboured five large conjugative plasmids encoding several multidrug resistance genes. The blaKPC-2 gene was located on a Tn3–Tn4401 composite transposon, which is part of a 65-kb multidrug-resistant IncN plasmid. The mcr-1 gene was harboured on another 33-kb IncX4 plasmid that was more conserved and presented few antimicrobial resistance determinants. No copies of insertion sequence ISApl1 were found flanking the mcr-1 gene, decreasing the mobility of mcr-1 based on its original Tn6330 transposon. Conclusions: Horizontal transfer of multidrug resistance plasmids or resistance-related transposon units was responsible for the emergence of this notorious superbug. The coexistence of blaKPC-2–IncN and mcr-1–IncX4 plasmids in a ST48 E. coli strain in humans poses a great threat.